Exploring the Metaphorical Significance of Death in Emily Dickinson's poem 'Because I Could Not Stop for Death' and Its Influence on 19th-Century American Poetry - Raza, Aqeel; Zahra, Nurjis (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research embarks on an exploration of the nuanced and evolving metaphorical representations of death within 19th-century American poetry focus on Emily Dickinson's poem 'Because I Could Not Stop for Death. The methodology integrates close textual analysis with historical contextualization, shedding light on the broader sociocultural landscape that influenced poetic expressions of death. By scrutinizing metaphorical intricacies, symbolism, and linguistic choices, the study aims to elucidate how Dickinson's portrayal of death diverges or aligns with the works of her peers. Moreover, it endeavors to discern underlying societal attitudes towards mortality, providing a comprehensive understanding of the intricate interplay between poetic representation and cultural dynamics in 19th-century American literature. In examining the metaphorical evolution of death in poetry, this research not only contributes to literary scholarship but also unveils broader insights into the cultural zeitgeist of the time, thereby enriching our understanding of the intricate relationship between poetic expression and societal perceptions of mortality.